PWE-075 Anti-tnf Therapy Reduces Ionising Radiation Exposure In Patients With Ulcerative Colitis. (9th June 2014) - Aggarwal, D; Limdi, JK
Abstract : Introduction: Patients with Ulcerative Colitis [UC] may be exposed to ionising radiation for evaluation of disease with inherent risks from protracted exposure. Meanwhile, bolder definitions of disease control with evolving treatment paradigms have led to earlier introduction of biological therapy. Our aim was to compare the effective radiation dose prior to and a year and 3 years after initiating anti-TNF therapy or corticosteroid in patients with UC. Methods: We performed a retrospective review of UC patients treated with anti-TNF therapy (infliximab or adalimumab) or corticosteroids at our institution from 2005 to 2013. Clinical data (demographics, disease characteristics, treatment) were obtained from case notes and electronic patient records. All instances of imaging in the previous year, 1 and 3 years after initiation of anti-TNF therapy were recorded. The effective and cumulative radiation doses were calculated from published tables [Royal College of Radiologists, UK]. Results: We analysed 102 patients with ulcerative colitis (66 anti-TNF and 36 corticosteroid treated). In the anti-TNF group, 68% were males (median age 47 yrs; range 25–76; mean disease duration 9.5 yrs). Forty seven per cent had left sided disease [Montreal E2] and 55% had pancolitis [Montreal E3]. In the corticosteroid treated patients, 55% were males (median age 51 yrs; range 17–90; mean disease duration 7.7 yrs). Montreal classification of disease was E1 in 11%, E2 in 46% and E3 in 43% respectively. The anti-TNF cohort had a significant reduction in the number of imaging studies (4.0 vs. 1.5, p < 0.0001) and cumulative radiation dose (4.1 vs. 1.1 mSv, p < 0.0001) a year after treatment. The corticosteroid group had no significant change in the number of imaging studies (1.9 vs. 1.3, p = 0.1 or cumulative radiation dose (3.2 vs. 2.0 mSv, p = 0.5). After 3 years of anti-TNF (n = 22), there was a reduction in the cumulative radiation dose (1.6 vs. 1.0 mSv, p = 0.3) and number of imaging studies (2.7 vs. 1.9, p = 0.3). In the corticosteroid group, there was a reduction noted in the cumulative radiation dose (2.5 vs. 1.1 mSv, p < 0.3) and no change in the number of imaging studies (1.6 vs. 1.7, p = 0.5). Linear regression analysis showed a decrease in cumulative radiation dose by 3.1 mSv (CI= -4.9 to +0.2, p = 0.07) and number of CT imaging scans by 1 (CI= +1.5 to -1.2, p < 0.08) in the anti-TNF group compared to the corticosteroid group within a year of therapy after adjusting for age, gender, disease duration, disease location and disease behaviour. Conclusion: Anti-TNF therapy is associated with a significant reduction in cumulative radiation dose and diagnostic imaging studies a year after anti-TNF therapy but not with corticosteroids. The decrease in radiation dose exposure in both groups was similar three years after treatment. Disclosure of Interest: None Declared.